ANALISIS PENGARUH CITRA WIRAUSAHA DAN SIKAP TERHADAP WIRAUSAHA TERHADAP MINAT BERWIRAUSAHA - Kukuh Mulyanto (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2016)
This study aims to investigate factors that influence entrepreneurialintentions of college students. The analysis model includes entrepreneurimage, and attitude. The research involves a sample of 96 students from 2faculties at STIE Totalwin Semarang by using anconvenience samplingtechnique. The results show a significant effect of the attitude, andentrepreneur image on the entrepreneurial intention of students. Likewise,this research also indicates the role of the contextual factors, such asacademic support and social support in determining the entrepreneurialintentions of students.